2022
DOI: 10.3389/fonc.2022.864021
|View full text |Cite
|
Sign up to set email alerts
|

Ascitic Senescent T Cells Are Linked to Chemoresistance in Patients With Advanced High-Grade Serous Ovarian Cancer

Abstract: Senescent T cells are reported to be increased in patients with cancer and are poor prognostic indicators. However, the distribution of senescent T cells and their correlation with clinical features in high-grade serous ovarian cancer (HGSOC) is unknown. We detected the percentage of senescent T cells in the peripheral blood and ascites of patients with advanced HGSOC (n = 86) at diagnosis by flow cytometry. Compared with healthy donors, patients with HGSOC exhibited an accumulation of CD28−CD57+ (Tsen) CD8+ T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Our preliminary work found increased senescent CD8 + PBLs of advanced HGSOC patients compared with healthy volunteers, suggesting that T-cell senescence may be associated with cancer diagnosis. However, senescent CD8 + PBLs showed no correlation with progression free survival in advanced HGSOC [20].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our preliminary work found increased senescent CD8 + PBLs of advanced HGSOC patients compared with healthy volunteers, suggesting that T-cell senescence may be associated with cancer diagnosis. However, senescent CD8 + PBLs showed no correlation with progression free survival in advanced HGSOC [20].…”
Section: Discussionmentioning
confidence: 87%
“…Nevertheless, senescent CD8 + TALs were closely associated with cancer progression [20]. Therefore, it is of great value to analyze the dysfunctional status of T-cells in the tumors and ascites of HGSOC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we are reporting this for the first time. Nevertheless, malignant body fluid in ovarian cancer is already showing promise both as a predictor of disease progression and as a substrate for monitoring drug response in immune target therapy [ 31 , 32 , 33 ]. Lane et al studied inflammation-regulating factors in ascites with advanced serous epithelial ovarian carcinoma [ 31 ] and found that IL-6 has a significant association with PFS in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al revealed that targeted cytokine (INF-gamma) expression level in ascites could serve as an immune biomarker for predicting outcomes in ovarian cancer [ 32 ]. Moreover, in a study by Zhang and colleagues, a high level of senescent T cells in ascites showed positive correlations with a short PFS and chemoresistance in advanced high grade serous ovarian cancer [ 33 ]. Of course, the generation of cell-mediated immune response depends on interactions of various cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Also, ovarian cancer affects the quality of life of patients. It is also related to many mechanisms, such as the angiogenic effects in ovarian cancer and mesothelial cells induced by Cu [ 6 ], high expression of Tsen CD8 T cells in ascites [ 7 ] and invasion of malignant ascites-derived EVs [ 8 ]. Hence, there is an urgent need to study the pathogenesis of this disease and discover sensitive and efficient markers for its effective diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%